The mTOR downstream regulator (p-4EBP1) is a novel independent prognostic marker in ovarian cancer. (19th May 2019) - Alabdullah, M. L.; Ahmad, D. A.; Moseley, P; Madhusudan, S.; Chan, S; Rakha, E.
Abstract: Ovarian cancer is associated with the highest mortality rate among gynaecologic malignancies. There is a need to refine the classification of ovarian cancer and identify novel targets. The mammalian target of rapamycin (mTOR) pathway has a crucial role in the pathogenesis and progression of ovarian cancer. This study aims to investigate the prognostic role of p-mTOR and its major downstream effectors p-4EBP1 (eukaryotic initiation factor 4E-binding protein 1) and p-P70S6K (ribosomal protein S6 kinase) in ovarian cancer. p-mTOR, p-4EBP1 and p-P70S6K protein expression was assessed on 195 consecutive ovarian epithelial cancers and correlated to clinicopathological features and survival. We found that high cytoplasmic expression of p-4EBP1 and p-P70S6K was associated with a serous type carcinoma ( p = .005) and an advanced FIGO stage ( p = .012), respectively. Univariate outcome analysis showed an inverse association between a high expression of p-4EBP1 expression and overall ovarian cancer survival (OS; p = .005) and progression-free survival (PFS; p = .005). p-P70S6K showed an inverse association with PFS ( p = .001). Multivariate analyses indicated that p-4EBP1 was an independent predictor of both OS and PFS ( p = .016 and p = .041, respectively). Therefore, we concluded that p-4EBP1 high protein expression is an independent predictor of outcome in ovarian cancer patients. Therefore, it could be used as a potential biomarker for prognostic stratification and treatment decisions. Impact statement: What is already known on this subject? The mammalian target of rapamycin (mTOR) pathway has a crucial role in the pathogenesis and progression of ovarian cancer. To-date, very limited knowledge is known about the importance of mTOR major downstream effectors p-4EBP1 (eukaryotic initiation factor 4E-binding protein 1) and p-P70S6K (ribosomal protein S6 kinase) in ovarian cancer. What do the results of this study add? In this study, we have provided further evidence of the adverse prognostic behaviour associated with the positive expression of p-mTOR and its major downstream effectors. Moreover and by performing multivariate analysis, we for the first time have proved that p-4EBP1 is an independent predictor of clinical outcome in ovarian cancer. What are the implications of these findings for clinical practice and/or further research? p-4EBP1 could be used as a potential biomarker for prognostic stratification and treatment decisions in ovarian cancer management.